2016
DOI: 10.1080/00140139.2016.1189599
|View full text |Cite
|
Sign up to set email alerts
|

The effect of individual differences in working memory in older adults on performance with different degrees of automated technology

Abstract: A leading hypothesis to explain older adults' overdependence on automation is age-related declines in working memory. However, it has not been empirically examined. The purpose of the current experiment was to examine how working memory affected performance with different degrees of automation in older adults. In contrast to the well-supported idea that higher degrees of automation, when the automation is correct, benefits performance but higher degrees of automation, when the automation fails, increasingly ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…However, this has not been the case. Pak et al (2016) found that when automation was reliable, as expected, older adults' performance was enhanced. However, they did not observe a performance decrease when automation failed, as was expected.…”
Section: Older Adults and Automated Technologysupporting
confidence: 72%
See 4 more Smart Citations
“…However, this has not been the case. Pak et al (2016) found that when automation was reliable, as expected, older adults' performance was enhanced. However, they did not observe a performance decrease when automation failed, as was expected.…”
Section: Older Adults and Automated Technologysupporting
confidence: 72%
“…The subsequent automation errors were randomly distributed among the remaining trials for each block. The participant continued to the next trial once they submitted their pairing or after 13 seconds elapsed or 20 for older adults (Pak et al, 2016), whichever comes first. Each block contained either information analysis, medium-decision, or high-decision automation and blocks was randomized for each participant.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations